Answer: No (-3,3) is not a solution to y = -3x
========================================================
Step-by-step explanation:
The point (-3,3) means x = -3 and y = 3 pair up together
So plugging in x = -3 should lead to y = 3 if (-3,3) was a solution
Plug x = -3 into y = -3x to find that
y = -3x
y = -3*(-3)
y = 9
So x = -3 and y = 9 should be the actual pair (not x = -3 and y = 3)
---------------
Put another way
y = -3x
3 = -3(-3) ... replace x with -3 and y with 3
3 = 9 ... which is false
This shows (x,y) = (-3,3) is not a solution